O ensino de língua portuguesa no contexto multilíngue de Foz do Iguaçu: uma proposta didática - Veber, Rosa Maria Ferreira (2024)
The presence of languages in contact within the context of schools in border regions contrasts with their internal silencing. The linguistic diversity presents itself as a challenge in the Brazilian educational context, in which the prevalence of monolingualism is still extremely practiced. The present research is focused on the theme of schools inserted in specific multicultural and multilingual contexts. Thus, we propose, in this study, an action research, because it enables planned participation of the researcher in the investigated situation. Therefore, we question: is it possible in Portuguese Language classes to reflect on the existing multilingual context in the border context of Foz do Iguaçu? And: how can Portuguese Language classes contribute to the welcoming and inclusion of students from Paraguay – Paraguayans and Brasiguaios – in a state school in the city of Foz do Iguaçu? From the research questions, emerges the main objective: to carry out and evaluate the work of a didactic proposal for Portuguese language for the multilingual context, in high school of a public school in Foz do Iguaçu. We justify the investigation due to the scarcity of an approach and of didactics that w elcome and include migrant students in our schools. Related to the epistemological affiliation, it is a social nature research belonging to Applied Linguistics, with a qualitative approach and an interpretivist character of the action-research type. Regarding the methodological way, we follow the steps, according to the specific objectives: to conduct a literature review on multilingualism, Portuguese language teaching, and the new high school; interpret and analyze the data obtained from interviews with Brazilian, Paraguayan, and Brasiguaio students; and, finally, to formulate, apply, and analyze a didactic proposal on the theme of multilingualism. The data-generating instruments used were semistructured interviews and observations by the teacher-researcher recorded in a field diary. The generated data, interpreted and discussed in the light of Applied Linguistics references – notably the Portuguese language research from the dialogical perspective of language, by the postulates of Bakhtin's Circle – indicated that, through the teacher's intervention, it is possible to welcome, integrate, and include migrant students in Portuguese Language classes. As a direct contribution of the research, it results the development of a didactic proposal for the welcoming and inclusion of migrant students in public schools in the border region.